Warmer Weather Linked to Tick Attack and Emergence of Severe Rickettsioses - Parola, Philippe; Socolovschi, Cristina; Jeanjean, Luc; Bitam, Idir; Fournier, Pierre-Edouard; Sotto, Albert; Labauge, Pierre; Raoult, Didier (PLOS Neglected Tropical Diseases, 2008)
Author Summary The impact of climate on the behaviour of the worldwide dog tick Rhipicephalus sanguineus is a cause of concern. This tick is a vector for life-threatening organisms including Rickettsia rickettsii, the agent of Rocky Mountain spotted fever, R. conorii, the agent of Mediterranean spotted fever, and the ubiquitous emerging pathogen R. massiliae. A focus of spotted fever was investigated in France in May 2007. One patient was found to be infected by R. conorii, whereas the other was infected by R. massiliae. Theses cases were original because of ophthalmic involvements, and the report of the second case of R. massiliae infection in the scientific literature. During an entomological survey, dense populations of Rh. sanguineus were found in the house where the patient had been bitten by ticks. Ticks were infected with either R. conorii or R. massiliae. Interestingly, April 2007 was the warmest since 1950, with summer-like temperatures. In this work, we show that the human affinity of Rh. sanguineus is increased in warmer temperatures, and provide evidence that this cluster of cases was related to a warming-mediated increase in the aggressiveness of Rh. sanguineus, leading to increased human attacks. From a global perspective, we predict that as a result of globalisation and warming, more pathogens transmitted by the brown dog tick may emerge in the future.